Strengthening Rural Community Job Readiness through Curriculum Vitae Writing and Job Interview Training Programs - Basyiruddin; Luluk Suci Ramandhani; Adinda Dwi Kurnia (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to improve the knowledge, skills, and confidence of job seekers in preparing curricula vitae (CVs) and facing job interviews in order to enhance job readiness. The program was conducted across eight strategic villages in Gresik Regency, East Java Province, namely Watuagung, Tanjung Widoro, Kramat, Karangrejo, Bedanten, Banyuwangi, Manyarejo, and Manyarsidomukti. A total of 108 respondents with diverse educational backgrounds, ranging from secondary education to bachelor’s degrees, participated in the activity. All participants were classified as job seekers at the time of program implementation. The community service method employed participatory training and experiential learning through three stages: diagnosis, intervention, and evaluation. The results showed an improvement in participants’ understanding of the function and structure of CVs. The effectiveness of the program was demonstrated by 90% of participants successfully producing industry-standard, ATS-compliant CVs. This achievement was supported by a significant increase in average scores from 68.11 to 87.11, indicating substantial progress in both cognitive and technical competencies. In addition, participants showed improvements in the quality of their CVs, communication skills, and confidence during job interview simulations. In conclusion, the CV writing and job interview workshops proved effective as a form of community service in improving the job readiness and competitiveness of rural communities in the labor market, with potential positive impacts in both the short and long term.